2014
DOI: 10.1590/s0034-8910.2014048005022
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative mortality of Aedes aegypti larvae treated with compounds

Abstract: OBJECTIVE To evaluate the larvicidal activity of Azadirachta indica, Melaleuca alternifolia, carapa guianensis essential oils and fermented extract of Carica papaya against Aedes aegypti (Linnaeus, 1762) (Diptera: Culicidae).METHODS The larvicide test was performed in triplicate with 300 larvae for each experimental group using the third larval stage, which were exposed for 24h. The groups were: positive control with industrial larvicide (BTI) in concentrations of 0.37 ppm (PC1) and 0.06 ppm (PC2); treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
4
1
2
Order By: Relevance
“…Larval mortality increased at higher extract concentrations, whereas in the negative control, there was no larval mortality because it did not contain ethanol extract of E. indica leaves. In this study, LC50 and LC90 were obtained at concentrations of 466.907 g/L and 868.42 g/L, different from research conducted [20] that at a concentration of 0.9093 g/L, E. indica leaf extract had the effect of killing 50% of the Aedes aegypti larvae population in 24 hours. Differences in outcomes E. indica leaf larvicide can be influenced by the location where the E. indica plant grows.…”
Section: Aedes Aegypti Larvaecontrasting
confidence: 58%
“…Larval mortality increased at higher extract concentrations, whereas in the negative control, there was no larval mortality because it did not contain ethanol extract of E. indica leaves. In this study, LC50 and LC90 were obtained at concentrations of 466.907 g/L and 868.42 g/L, different from research conducted [20] that at a concentration of 0.9093 g/L, E. indica leaf extract had the effect of killing 50% of the Aedes aegypti larvae population in 24 hours. Differences in outcomes E. indica leaf larvicide can be influenced by the location where the E. indica plant grows.…”
Section: Aedes Aegypti Larvaecontrasting
confidence: 58%
“…The results of this study were consistent with those reported by Sneha (Sneha & Preet, 2016) that during the test, essential oils affected the test larvae which decreased the frequency of larval movements. Decreased frequency of larval movements is the first sign that a material has larvacidal properties (Torres et al, 2014) The decrease in the frequency of larval movement is the effect of one of the compounds in kaffir lime peel essential oil namely monoterpene. Most essential oils of kaffir lime peel are monoterpene.…”
Section: Resultsmentioning
confidence: 99%
“…Themepos organofosfat adalah larvasida yang digunakan secara luas sebagai pengendalian vektor dengue di Martinique yang telah menunjukkan resistensi di Asia Tenggara, Amerika Selatan, dan Karibia. 5 Menurut Basimeye, jus daun mengkudu mengandung tanin sebanyak 5,12% saponin sebanyak 0,18%, dan flavonoid sebanyak 43,9%, dimana senyawa-senyawa tersebut dapat…”
Section: Pendahuluanunclassified